2020
DOI: 10.1585/pfr.15.2405008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydrocarbons in the Exhaust Gas of a Fusion Test Device Using Infrared Absorption Spectroscopy

Abstract: To investigate the behavior of hydrogen isotopes in a large fusion test device, a new technique using infrared absorption spectroscopy is applied for the monitoring of hydrocarbons in exhaust gas. Fourier transform infrared (FT-IR) spectroscopy combined with a gas cell, which has an optical path length of 16 m, was installed at the plasma exhaust line. In this configuration, the detection limit of CH 4 , C 2 H 6 , C 2 H 4 , and CO is at the level of sub-ppm. The exhaust gas observations were conducted during h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In the unstable operation region, acetylene, which was not detected during the glow discharge operation in a previous study [18], was observed. Additionally, the ratio of hydrogen atoms in the produced hydrocarbons, C x Q y , was higher.…”
Section: Production Of Deuterated Hydrocarbons During D 2 Glow Discharge During Wall Bakingmentioning
confidence: 57%
See 3 more Smart Citations
“…In the unstable operation region, acetylene, which was not detected during the glow discharge operation in a previous study [18], was observed. Additionally, the ratio of hydrogen atoms in the produced hydrocarbons, C x Q y , was higher.…”
Section: Production Of Deuterated Hydrocarbons During D 2 Glow Discharge During Wall Bakingmentioning
confidence: 57%
“…Hydrocarbons are produced by chemical sputtering of carbon tiles during the hydrogen isotope glow discharge operation. In a previous study [18], however, deuterated hydrocarbons (C x H y D z ) were not detected during D 2 glow discharge between LHD plasma experiments. Thus, the vacuum vessel is cleaned by the plasma experiments and wall conditioning operations, lowering impurity components such as water vapor.…”
Section: Ftir Spectra Of Ammonia and Deuterated Hydrocarbons During Wall Baking And D 2 Glow Dischargementioning
confidence: 61%
See 2 more Smart Citations